2022
DOI: 10.31681/jetol.925340
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of studies published in the field of augmented reality in education

Abstract: This review study was carried out using content analysis and it was aimed to analyze the articles published in national journals in the field of augmented reality. The sample of this study, in which the content analysis method was used, consists of 87 academic studies conducted in the field of augmented reality in education in Turkey between 2012 and 2020. Studies obtained as a result of scanning were analyzed according to some variables such as the publication year, purpose, subject area, approach / method, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The analysis yielded a discernible outcome indicating that the number of the studies increased each year. Differently than Kapucu and Yıldırım's (2019) results, Turhan et al (2022) found that majority of the studies were conducted on the field of science education.…”
Section: Purpose Of the Studymentioning
confidence: 69%
See 3 more Smart Citations
“…The analysis yielded a discernible outcome indicating that the number of the studies increased each year. Differently than Kapucu and Yıldırım's (2019) results, Turhan et al (2022) found that majority of the studies were conducted on the field of science education.…”
Section: Purpose Of the Studymentioning
confidence: 69%
“…Over the last few decades, AR technologies and their applications to education have burgeoned throughout various fields in Turkey as in the world. Consequently, several systematic reviews have been conducted to investigate the picture of AR usage in a Turkish context (Kapucu & Yıldırım, 2019;Korucu, Ustan and Yavuzaslan, 2016;Turhan, Metin and Ezberci-Çevik, 2022). Among those studies, the parameters of Kapucu and Yıldırım's (2019) review were the years between 2010 and 2018.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Achievement tests are among the most commonly used data collection tools in recent studies on the use of AR technology in other education fields (Arıcı et al, 2019;Kara, 2018;Sırakaya & Alsancak Sırakaya, 2020;Turhan et al, 2022). However, when examining the data in Table 5, it can be seen that achievement tests were not used in any studies.…”
Section: Distribution Of the Studies According To The Data Collection...mentioning
confidence: 99%